Environmental regulation, industrial agglomeration, and sustainable development in the Chinese textile industry - Ju, Xiaoying; Ma, Zhida; Chen, Fei; Yao, Peng; Liu, Jianxu; Sriboonchitta, Songsak (Technological and Economic Development of Economy, 2023)
Is it possible for the imposition of environmental regulation to develop the textile industry? Is it possible to balance quality and efficiency with energy conservation and emission reduction and achieve the sustainable development of the textile industry? The main objective of this study is to analyze the effects of the environmental regulation on industrial agglomeration and industrial efficiency within the textile sector. The findings reveal that, first, environmental regulation has significantly facilitated the agglomeration of the textile industry to regions with less stringent environmental standards. The restructuring and optimization of domestic value chains have also been promoted. Second, environmental policies in the process of the promotion of the industrial agglomeration are accompanied by a significant improvement in industrial efficiency. This improvement has contributed to the achievement of sustainability goals in the textile domain. Third, the influence of environmental regulations on industrial agglomeration and industrial efficiency improvement of the textile industry is strongly heterogeneous in terms of ownership. This impact is more significant in state-owned industries and private industries. This study holds substantial theoretical significance and practical relevance in promoting environmentally friendly and sustainable progress in the Chinese textile industry.First published online 12 October 2023